The Analysis of Gene Expression on Fertility Decline in Caenorhabditis elegans after the Treatment with 5-Fluorouracil - Si ZHANG; Zhaolian LU; Hongmei LIANG; Ximei FU; Yan ZHANG; Xin LIU; Genshu BAO; Tao JING; Xuan WANG; Meng WANG; Julong WU; Gen CHEN (Tehran University of Medical Sciences, 2015)
Background: 5-Fluorouracil could lead to a decline in fertility in Caenorhabditis elegans. The aim of this study was to describe the mechanisms underlying such an altered fertility phenotype and to illustrate the specific genes and path-ways that are involved in the related phenotypic changes in C. elegans. Methods: We isolated total RNA from the samples and used a new method called Digital Gene Expression (DGE), which can rapidly identify genes with altered transcript levels. The random genes were confirmed by real-time RT-PCR. Results: We analyzed the results of two methods to draw conclusions based on a comparison between C. elegans and other harmful parasites. Compared with controls, 1147 genes were up-regulated, and 1067 were down-regulated. Overall, 101 up-regulated genes had a log2 ratio higher than 8, whereas the log2 ratio of 141 down-regulated genes was higher than 8. After mapping to the reference database, 4 pathways were confirmed to be involved in this phe-nomenon, with statistically significant participation from 19 genes. Conclusion: For the first time, the transcript sequence of 5-Fu-treated worms and controls was detected. We found that 4 possible pathways, i.e., ECM-receptor interaction pathway, TGF-beta signaling pathway, Focal adhesion and Hypertrophic cardiomyopathy, may be involved in the number decline in the embryos of C. elegans. Specifically, the ECM-receptor interaction pathway and Focal adhesion may be very important pathways that alter the reproduction of C. elegans.